A Comparative Study of Coronary Angiographic (CAG) Findings Between Diabetic and Nondiabetic Patients (Medicine Today, 2015)
Patients with diabetes mellitus have a higher prevalenceof atherosclerotic heart disease and a higher incidence of myocardialinfarction than the general population. Diabetic patients alsohave several hematologic, metabolic abnormalitiesnot present in their nondiabetic counterparts that may predisposethem to formation of morphologicallycomplex plaques. Percutaneous coronary angiography (CAG) was performedin 120 consecutive patients with suggestive of ischaemic chest pain. The populationconsisted of 45 (37.50%) diabetic and 75 (62.50%) nondiabetic patients. We observed positive angiographic lesion among both groups comparing site & number of vessel(s) involvement also average percentage of stenosis. The presence of coronary risk factors was not significantlydifferent between the two populations. Total positive angiographic lesion was 79 (65.83%) in both groups. Among the Diabetes mellitus patients positive CAG finding 37 (82.22%).The recognized lesions were single vessel disease (SVD) 10 (27.02),double vessel disease (DVD) 15 (40.54%), triple vessel disease (TVD) 12 (32.43%), diffuse lesions 4 (10.80%) and average vessel stenosis 83.63%.On the other hand, total positive angiographic lesion was 42 (56%) in nondiabetic group; among them single vessel disease (SVD) 14 (33.33%), double vessel disease (DVD) 17(40.47%),triple vessel disease (TVD) 11 (26.19%), no diffuse lesions was found and average vessel stenosis was 78.03%. The results of the angiographic finding suggest that diabetic patients have a higher incidenceof coronary heart disease (CHD), DVD, TVD, diffuse lesion & marked stenosis of coronary vessel than nondiabetic patient. This increased frequency of complex lesion morphology is more difficult to treat by definitive intervention like percutaneous transluminal coronary angioplasty (PCI) & coronary artery bypass graft (CABG).Medicine Today 2014 Vol.26(2): 95-99